2006
DOI: 10.1128/jcm.44.2.646-648.2006
|View full text |Cite
|
Sign up to set email alerts
|

Timely Diagnosis of Disseminated Toxoplasmosis by Sputum Examination

Abstract: The diagnosis of disseminated toxoplasmosis in a 14-year-old allogeneic bone marrow recipient with graftversus-host disease was determined by the detection of Toxoplasma gondii tachyzoites in sputum smears. Sputum analysis is a valuable alternative in the clinical assessment of pulmonary toxoplasmosis, especially when conventional invasive techniques are not practicable. CASE REPORTA 14-year-old girl had been transplanted with human lymphocyte antigen-identical allogeneic hematopoietic stem cells from an unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Cell culture offers the possibility of reducing this delay, but is no longer used for diagnosis, since the development of DNA‐based diagnostic methods. PCR techniques, the most sensitive of which involve the repeated B1 and AF146527 gene targets, have markedly changed the strategy for diagnosis and treatment of transplant recipients [42,64–68]. Moreover, the use of real‐time PCR avoids the risk of false positivity due to DNA carryover [65], and allows quantification of T. gondii DNA to monitor treatment efficacy [50].…”
Section: Diagnosismentioning
confidence: 99%
“…Cell culture offers the possibility of reducing this delay, but is no longer used for diagnosis, since the development of DNA‐based diagnostic methods. PCR techniques, the most sensitive of which involve the repeated B1 and AF146527 gene targets, have markedly changed the strategy for diagnosis and treatment of transplant recipients [42,64–68]. Moreover, the use of real‐time PCR avoids the risk of false positivity due to DNA carryover [65], and allows quantification of T. gondii DNA to monitor treatment efficacy [50].…”
Section: Diagnosismentioning
confidence: 99%
“…Toxoplasmosis is a rare, but potentially life‐threatening opportunistic infection, with an estimated mortality rate of 60–90%, after allogeneic hematopoietic stem cell transplantation (allo‐SCT) , and has been attributed to the reactivation of latent Toxoplasma gondii infection . The seroprevalence of T. gondii varies markedly among different regions, ranging from 10% to 50–80%; 10% in Japan, <15% in the United States, and 50–80% in Central Europe .…”
mentioning
confidence: 99%
“…However, PCR for T. gondii is a time-consuming method because it is not performed routinely in Japan. Laibe et al reported a case of disseminated toxoplasmosis diagnosed using a Diff-Quick-stained sputum smear analysis (16). Sputum is readily obtainable, even from severely ill patients, and its analysis can be performed immediately.…”
Section: Discussionmentioning
confidence: 99%